(untitled) (Practitioner Research, 2019)
This research examined the relationship between five areas of cognitive autonomy and development among adolescents. Students from middle and high school in Kedah participated in this study and ninetyfour participants responded on the Cognitive Autonomy and Self- Evaluation (CASE) inventory, which examined the evaluative thinking, voicing opinions, comparative validation, decision making, and selfassessment. Scores were compared based on gender and grades. Results highlighted that high school students scored significantly higher in two of the five areas of cognitive autonomy. Additionally, female students in middle school rated themselves significantly higher in two areas of cognitive autonomy (evaluative thinking and decision making). Areas of academic grades, time watching TV, time spent reading, and using computer are also discussed.